Development of Digital Marketing Technology to Increase Sales in the MSMEs of the Neera Palm Sugar Palm Oil Business in Perbaungan District Melati II Village - Tria Wardani; Nurbaiti Nurbaiti; Muhammad Ikhsan Harahap (Sharia Economics Department Universitas KH. Abdul Chalim, Mojokerto, 2023)
The marketing of MSMEs products, neera palm sugar, and palm oil in the Perbaungan District is considered to be inefficient. The reason is that the MSMEs owners of neera palm sugar, and palm oil in Perbaungan District do not yet have optimal capabilities in managing digital marketing technology as a tool to market their products. This research aims to know the knowledge of MSMEs business actors neera palm sugar palm oil, regarding sales based on digital marketing to increase sales of neera palm sugar palm oil. The research method used is a qualitative research method using a qualitative descriptive survey method. The data source used is the results of direct interviews with respondents as well as some relevant literature used as a secondary data source. The results of the study show an efficient way for MSME players to know the urgency of using digital marketing technology as a marketing tool through direct socialization and practice in using the marketplace.